2001
DOI: 10.1007/s004390100458
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in promoter region of Fcα receptor gene in patients with IgA nephropathy

Abstract: We have recently identified two novel polymorphisms (-114T/C and +56T/C relative to the major transcription start site) in the functional promoter region of the Fcalpha receptor (FcalphaR) gene. Since altered FcalphaR expression may be associated with IgA nephropathy, we examined these promoter polymorphisms in this disease. Patients with IgA nephropathy (n = 90), patients with other primary glomerulonephritis (n = 50), and healthy adults (n = 83) were studied. Genotyping was performed by the polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…It is possible that our study population was not large enough to produce statistically significant results. Nonetheless, the numbers of patients with IgAN and with other types of glomerulonephritis analyzed in this study were much larger than a previous report that showed a significant difference between the genotype and allele distributions of the two groups (Tsuge et al 2001). The number of subjects with IgAN was 151 in the present study, but only 90 in the previous study.…”
Section: Resultscontrasting
confidence: 78%
“…It is possible that our study population was not large enough to produce statistically significant results. Nonetheless, the numbers of patients with IgAN and with other types of glomerulonephritis analyzed in this study were much larger than a previous report that showed a significant difference between the genotype and allele distributions of the two groups (Tsuge et al 2001). The number of subjects with IgAN was 151 in the present study, but only 90 in the previous study.…”
Section: Resultscontrasting
confidence: 78%
“…Growing evidence has shown that genetic polymorphisms of FcR and consequent alteration of their function may affect the prognosis of these IC diseases (1)(2)(3). In the last decade experimental studies, particularly with different knockout strains of animals, have revealed that FcR are crucial molecules providing a critical link between ligands (IC) and effector cells in IC-mediated inflammatory cascade (4,5).…”
Section: Mmune Complex (Ic)mentioning
confidence: 99%
“…To analyze in detail the cell type specificity of this region, 5Ј and 3Ј truncation mutants were fused to the firefly luciferase gene and transfected into various cell lines. In our previous papers (11,12), we numbered nucleotide positions from the major transcription site that had been identified by de Wit et al (20). However, since the Fc␣R promoter appears to contain multiple transcription start sites (20) (our unpublished observations), we hereafter designate the ATG translation initiation codon as ϩ1.…”
Section: The Fc␣r Promoter Contains a Myeloid-specific Essential Regumentioning
confidence: 99%